Efficacy, safety, and immunogenicity of Lassa fever vaccines: A living systematic review and landscape analysis of vaccine candidates - Bardach, Ariel; Berrueta, Mabel; Ciapponi, Agustín; Sambade, Juan M.; Castellana, Noelia; Ballivian, Jamile; Brizuela, Martín; Caravario, Julieta; Comande, Daniel; Couto, Esteban; Mazzoni, Agustina; Ortega, Vanesa; et al. (PLOS ONE, 2025)
Background Lassa fever (LF) is an acute viral hemorrhagic illness endemic in West Africa, representing significant public health challenges, particularly for pregnant persons and children who experience higher morbidity and mortality. Although several vaccine candidates are being developed, no LF vaccine has been licensed yet. Methods We conducted a living systematic review (LSR) of the literature to evaluate the safety, efficacy, effectiveness, and immunogenicity of LF vaccines. We performed biweekly searches in major biomedical databases, trial registries, preprint servers, and other sources. Eligible studies included preclinical studies, clinical trials, and observational studies published from January 2014 to April 2025. Reviewer pairs screened studies extracted data (REDCap), and assessed risk of bias independently. Data synthesis involved random-effects pairwise and proportion meta-analyses (R software), with GRADE assessment of evidence certainty. PROSPERO registries: (CRD42024514513; CRD42024516754). Results Searches retrieved 1423 records, including 51 studies, 2 clinical trials in adults involving 88 vaccinated persons, and 49 preclinical studies of 30 vaccine candidates. Trials evaluated Recombinant Measles-Vectored (MV-LASV) and Recombinant Vesicular Stomatitis Virus-based (rVSVΔG-LASV-GPC) LF vaccine candidates. No published clinical trials were found to evaluate LF vaccines in special populations such as pregnant persons, infants, children, or adolescents. Although injection site reactogenicity was reported, no vaccine-related serious adverse events (SAEs) were reported in study participants. Immunogenicity was robust in adults, with vaccines achieving around 95% seroconversion at 30 days. Preclinical data evaluated nine different platforms. Findings are disseminated via an interactive online dashboard (https://safeinpregnancy.org/living-systematic-review-lassa/). Conclusion Currently, two LF vaccine candidates that have advanced to clinical trials exhibit high immunogenicity, but the safety profile in healthy adults is still limited. Clinical evidence in pregnant persons, infants, children, and adolescents is absent. Vaccine platforms of interest have been identified in preclinical studies, providing information on those that could advance to clinical studies.